Pengembangan Media Layanan Berbasis Aplikasi Android Tentang Informasi Studi Lanjut pada Siswa SMP Muhammadiyah 2 Yogyakarta - Cindy Fitriadita; Akhmad Fajar Prasetya (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This study aims to develop an Android application-based service media called INSTULA that provides information related to further study to grade IX students of SMP Muhammadiyah 2 Yogyakarta. Further study information is defined as a collection of data, knowledge, and guidance that helps students understand and choose further education paths according to their potential, interests, talents, and future career prospects. This application contains features such as types of secondary schools (SMA, SMK, MA), interests, simple aptitude tests, and job prospects. The research model used is Research and Development (R&D) with the Borg and Gall approach which is carried out up to the seventh stage, namely product revision. The development process involves validation by material experts, media experts, and service experts. The total results of the expert assessment showed an average score of 90.7 out of 100, with the category